Physicochemical properties of Nickel Picolinate Complexes - Ben-Aweisha, Abd-Elrahim; Abu-Youssef, Morsy A.; Mansour, Saber E.; ElMagbari, Fatin M. (Al-Mukhtar Journal of Sciences, 2010)
In the present work, the complexes were synthesized by the interaction between the picolinic acid with Ni(II) metal ions, then salted-in. The geometrical structures and the chemical formula of the complexes were characterized by several techniques; such as, elemental analysis, molar conductivity, FT-IR spectroscopy, and thermal analysis and thermodynamical parameters. The complexes after salting-in were fairly stable under normal atmospheric condition. The salting-in of Nickel picolinate complexes in different simple salts, KI and Guanidinium hydrochloride, gives the same structure. For the two nickel complexes TGA were thermally decomposed in four successive steps, leaving NiO residue at >55OCº, Thermodynamic parameters for the decomposition steps, by employing the CR and HM equations, the thermal stability of the complex reflected ftom the high values of the ∆E* the negative sign of the ∆S*.